Digging for data: How sleep is losing out to roster design, sleep disorders, and lifestyle factors. (February 2022) - Maisey, Gemma; Cattani, Marcus; Devine, Amanda; Lo, Johnny; Fu, Shih Ching; Dunican, Ian C.
Abstract: Shift workers employed at a remote mining operation may experience sleep loss, impaired alertness, and consequently negative health and safety outcomes. This study determined the sleep behaviors and prevalence of risk for sleep disorders among shift workers; and quantified alertness for a roster cycle. Sleep duration was significantly less following; night shift by 77 ± 7 min and day shift by 30 ± 7 min. The wake after sleep onset was less by 23 ± 3 min for night shifts and 22 ± 3 min for day shifts (p < 0.05 for all). The prevalence of risk for sleep apnea was 31%, insomnia was 8%, and shiftwork disorder was 44%. Average alertness for all working hours was 75%. Shiftwork in remote mining operations is a significant factor that leads to sleep loss and reduced alertness, which is exacerbated by the high prevalence of risk for sleep disorders. Highlights: Shift start times <06:00, may result in sleep loss resulting in poor alertness. Prevalence of shiftwork disorder and obstructive sleep apnea in mining is high. Risk of sleep disorders increased with body mass and age. Biomathematical modeling may be used to eliminate or reduce organizational risk.